2011
DOI: 10.1007/s11104-011-0719-9
|View full text |Cite
|
Sign up to set email alerts
|

Sites, pathways, and mechanism of absorption of Cu-EDDS complex in primary roots of maize (Zea Mays L.): anatomical, chemical and histochemical analysis

Abstract: To study the mechanism of chelant-metal complexes to be absorbed into plant roots in the presence of different concentration chelating agents, the sites, pathways, and mechanism of absorption of Cu-EDDS complex ([S, S']-ethylene diamine disuccinic acid) in maize (Zea mays L.) primary roots were systematically studied. The results showed that, at low concentrations of the Cu-EDDS complex (<200 μmol L −1 ) in hydroponic culture, the complex was passively absorbed mainly from the apoplastic spaces where lateral r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…In a recent study with Zea mays [ 12 ], the chelator EDDS was found to increase cell membrane permeability, with a concomitant increase in shoot concentrations. Although this was attributed to expansion of the apoplastic pathway through injured passage cells [ 72 ], rather than to increased solute entry into the symplast, it indicates that strong chelating agents can permeabilize plant cell membranes. This supports the findings of the experiments and model simulations.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study with Zea mays [ 12 ], the chelator EDDS was found to increase cell membrane permeability, with a concomitant increase in shoot concentrations. Although this was attributed to expansion of the apoplastic pathway through injured passage cells [ 72 ], rather than to increased solute entry into the symplast, it indicates that strong chelating agents can permeabilize plant cell membranes. This supports the findings of the experiments and model simulations.…”
Section: Resultsmentioning
confidence: 99%
“…At root tips it is not fully formed, and at the site where lateral roots protrude from the main root the Casparin strip can be disrupted. Niu et al (2011) demonstrated in the hydroponic culture of Z. mays that at low concentrations the Cu-EDDS complex (200 lM) was passively absorbed mainly from the apoplastic spaces where lateral roots penetrate the endodermis. At higher concentrations (3,000 lM), the passage cells which form a physiological barrier controlling ion absorption were injured and substantially larger quantities of this complex could enter the root xylem.…”
Section: Discussionmentioning
confidence: 99%
“…Tian et al [35] detected Pb-EDTA in the vascular bundles of both leaf and stem tissues in the accumulator plants using synchrotron-based x-ray microfluorescence and powder extended x-ray absorption fine structure (EXAFS) spectroscopy. It has been concluded that the uptake of Pb-EDTA by the plant roots is possible at locations where the suberization of root cell walls has not yet occurred and at breaks in the root endodermis and the Casparian strip [36][37]. It has been suggested that the metal-chelant complexes might enter the xylem vessels for translocation to the aboveground plant parts through passive pathways that use transpiration pull as the main driving force [38].…”
Section: Mechanism Of Plant Absorptionmentioning
confidence: 99%